Բարբառային օրինաչափությունների պահպանման կարևորությունը բանահյուսական ժողովածուներում - Սարգսյան, Ա. Յու.
В статье представлены нарушения диалектических закономерностей в фольклорных сборниках на примере Карабахского диалекта. Автор подчеркивает важность сохранения диалектических закономерностей, в частности транскрипции в фольклорных сборниках, что обеспечит надежность подобных источников при исследовании армянских диалектов. Одновременно рассматриваются факторы, обуславливающие искажения диалектических закономерностей. The article presents breaches of dialectal regularities in folklore collections on the example of Karabagh dialect. The author considers importance of preserving dialectal regularities, in particular preverving transcription in folklore collections, which will result in trustfulness of similar collections in the study of Armenian dialects. Simultaneously, the article regards the factors determining the distortion of dialectal regularities.
Keywords: Հայոց լեզու, բառբառագիտություն